Implementation of Green Practices: The Role of Knowledge and Financial Resources - Sharma, Vriti (European Journal of Sustainable Development, 2025)
Companies have made profits by causing environmental pollution, but now there is a global push for green development. As a part of this shift, green practices are becoming increasingly important for businesses to help protect the environment. Many studies have explored the benefits of green practices, yet discussions often focus on their advantages but overlook key factors needed for successful implementation. This research aims to address this gap by examining the “how” and “what” required to implement green practices, specifically focusing on knowledge and financial resources. These factors are the basic requirements for implementing new initiatives. Knowledge is important because without proper knowledge, businesses may struggle to implement effective strategies, and without financial resources, they may lack the means to invest in green practices. To understand the importance of these factors, this research utilizes Qualitative Comparative Analysis using survey data from 60 participants in the UK and Germany from 2,788 energy-intensive companies. The findings show that internal knowledge is important for successfully implementing green practices. The findings also highlight the importance of a company's financial stability for successfully implementing green practices. Even with access to external funding resources, post-implementation outcomes may be less effective if internal financial stability is weak. Keywords: Green Practices, Financial Resources, Knowledge, Green Practices Implementation